UNCONSTRAINED CITY DEVELOPMENT USING THE EXTENSION OF STOCHASTIC EDEN SIMULATION - K. Teknomo; G. P. Gerilla; K. Hokao; L. Benguigui (International Association of Lowland Technology, 2005)
In the quest for a special tool for lowland urban growth model, we have developed a model of a city based on the analogy of biological cell growth using the extension of the stochastic growth Eden simulation. In this paper, we described the theoretical observable fact on how a city grows if the land is flat and there is no natural barrier for the development. Similar researches on cellular urban growth are reviewed and we showed how they are different from our model. Urban growth model development using the extension of the Eden model as analogues to biological cell growth is explained. The model is applied to simulate a hypothetical unconstrained city development. The simulation results shows that for a mono-centric city without any development constraint, the expansion rate of the city area is equivalent to the ratio of the perimeter per area of the city. This result may be useful to predict the approximategrowth rate of any city without any prior knowledge of the historical data. Furthermore, it was found that the growth of an unconstrained city is almost circular with a decreasing rate of the mean radius growth.